Comparing the Relative Impact of Smartwatch and Smartphone Use While Driving on Workload, Attention, and Driving Performance. (September 2015) - Samost, Aubrey; Perlman, David; Domel, August G.; Reimer, Bryan; Mehler, Bruce; Mehler, Alea; Dobres, Jonathan; McWilliams, Thomas
A simulator study evaluated the extent to which the use of a smartwatch to initiate phone calls while driving impacts driver workload, attention, and performance, relative to visual-manual (VM) and auditory-vocal (AV) calling methods on a smartphone. Participants completed four calling tasks using each method while driving in a simulator and completing a remote detection response task (R-DRT). Among the 36 participants evaluated, R-DRT miss rates and reaction time were comparable between AV calling on the smartwatch and smartphone, but significantly higher using VM calling on the smartphone. Participants also exhibited more erratic driving behavior (lane position deviation and major steering wheel reversals) with smartphone VM calling compared to both AV calling methods. Finally, participants rated AV calling on both devices as entailing lower workload than VM calling on the smartphone. Overall, few differences emerged for the metrics reported between voice calling on a smartphone versus a smartwatch while driving.